Oncological and Surgical Outcomes of Oncoplastic Reduction Mammoplasty: A Single-centre Retrospective Study - Martinea, Jérôme; Tekdogan, Boran; Lam, Giang-Thanh; Correia, Daniel; Giordano, Salvatore; Kalbermatten, Daniel F; Oranger, Carlo M (Anticancer Research USA Inc., 2025)
Background/aim: Breast-conserving surgery is the preferred treatment for early-stage breast cancer but can often result in unsatisfactory cosmetic outcomes. Oncoplastic surgery aims to improve both oncologic and aesthetic outcomes by combining local excision with plastic surgery techniques. Using breast reduction techniques in breast cancer treatment has been shown to allow for wider margins of excision, leading to enhanced oncological safety and reduced recurrence rates without causing significant asymmetry. This study aimed to analyze the surgical and oncological outcomes of a large cohort of patients undergoing oncoplastic reduction mammoplasty (ORM).
Patients and methods: A retrospective analysis of postoperative surgical and oncological outcomes of all patients who underwent ORM at a single center between January 2018 and December 2023 was performed. Preoperative patient characteristics, operative and post-operative outcomes were recorded and analyzed.
Results: A total of 67 patients that underwent oncologic breast reduction were included in the final analysis - representing a total of 71 ORM, with a mean (SD) age of 53.1 (10.5) years and a mean (SD) BMI of 28.8 (5.9) kg/m2 A superomedial pedicle-based technique was the most frequently used (36.6%), followed by inferior pedicle-based technique (28.1%). A complication rate of 18.3% on the ipsilateral side was observed. Salvage surgery was necessary in five cases (7.0%) due to positive margins - with one patient (1.4%) requiring margin expansion surgery and four (5.6%) a completion mastectomy.
Conclusion: This monocentric retrospective study shows that ORM is safe, with a complication rate on par with conventional breast reduction and offers satisfactory oncological outcomes.